Peran Modal Kemauan, Keterampilan, & Pengetahuan dalam Kewirausahaan - Nurhayani Nurhayani; Kezya Meylani Fernanda Putri; Ayuni Kartika; Yusawinur Barella (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
In entrepreneurship, to start a business, basic capital is required which must be owned by every individual who wants to become an entrepreneur. Without capital, a person cannot start a business. The capital that must be prepared can be from internal aspects or from within the individual, such as the desire from within to start entrepreneurship, the skills possessed to help run the business, and knowledge. Entrepreneurship also involves the ability to develop a business and solve problems. This journal was created with the aim of knowing the role of will capital, skill capital, and knowledge capital for someone who is about to start an entrepreneur. When someone will start entrepreneurship, of course, they need capital as one of the important factors that will support their business. This journal contains material on will capital, skill capital, and knowledge capital and its role in entrepreneurship. The method used in writing this journal is the literature method.